Impact of season, weekends and bank holidays on emergency department transfers of nursing home residents. (August 2016) - Fan, C.; Keating, T.; Brazil, E.; Power, D.; Duggan, J.
Abstract Background For urgent, unexpected clinical events, nursing home (NH) residents are transferred to the acute hospital emergency department (ED). A previous study showed that a third of transfers occurred during working hours. Aims Our aims were to profile a one-year NH transfers to the ED and to examine the re-presentation, patient-oriented outcome and the impact of season, weekends and bank holidays on NH transfers. Methods All NH transfers from a catchment to an ED over one year were identified using electronic patient record. Age, gender, reason for presentation, patient-oriented outcome and date and time of presentation were recorded. Representation and the interval between transfers were calculated. Number of transfers was calculated for season, weekdays/weekends and bank holidays. Studentt test, Chi-square statistics and one-way ANOVA were used. Significance was set at 0.05. Results There were 802 transfers from 465 NH residents over a year; 501 (62.5 %) resulted in admissions, 189 (40.6 %) residents represent to the service and 80 episodes occurred within a fortnight of the last attendance. The highest transfers occurred in May (2.81 patients/day), during working hours and on Wednesdays and Thursdays (>2.5 transfers/day). 'Unwell adult' and 'falls' were the two commonest reasons for presentation. Conclusions Our study showed that NH transfers occurred mainly within working hours and during weekdays. Insights into the transfer pattern and the reasons for NH patients to utilise ED will facilitate improved design and operation of the department by creating care pathways for these patients.